Investors’ net buying pressure and implied volatility dynamics - Doojin Ryu; Robert I. Webb; Heejin Yang; Jinyoung Yu (Borsa Istanbul Review, 2022)
This study reexamines the influence of different investor types' net options demand on the KOSPI200 options-implied volatility dynamics. We extend Bollen and Whaley (2004) by accounting for options traders' hedging demand for futures contracts, intraday seasonality, dynamic impacts of net buying pressure on implied volatility, and the effect of regulatory reform in the options market. Our empirical analyses provide evidence for the direction-learning behavior of foreign institutional investors. We further show that foreign institutions’ net demand is the most informative about the underlying market volatility independent of the market reform, while domestic retail investors become partially informed only after the reform.